2010
DOI: 10.4314/ajtcam.v6i2.57083
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic and antihyperglycaemic activity of <i>Ageratum conyzoides</i> l. In rats.

Abstract: The hypoglycaemic and antihyperglycaemic properties of the aqueous extracts of the leaves of Ageratum conyzoides L. were evaluated in normoglycemic and in streptozotocin-induced diabetic rats, in order to validate its use in folk medicine. Tested animals were given the aqueous extracts of the plant at the doses of 100, 200 and 300mg/kg. These doses were tested also on glucose loaded normal male rats (Oral Glucose Tolerance Test). Of all the doses, the aqueous extracts at 200 and 300mg/kg showed statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
0
21
1
Order By: Relevance
“…The extract may inhibit glucose absorption in gut (Bhowmik et al, 2009). Alternately, the extract may potentiate the pancreatic secretion of insulin or increase the glucose uptake (Farjou et al, 1987;Nyunai et al, 2009). Although the present study did not identify the chemical component(s) responsible for the observed antihyperglycemic effect, it may be noted that quercetin is one of the components reported to be present in khoyer (Rajendra et al, 2011).…”
Section: Resultscontrasting
confidence: 48%
“…The extract may inhibit glucose absorption in gut (Bhowmik et al, 2009). Alternately, the extract may potentiate the pancreatic secretion of insulin or increase the glucose uptake (Farjou et al, 1987;Nyunai et al, 2009). Although the present study did not identify the chemical component(s) responsible for the observed antihyperglycemic effect, it may be noted that quercetin is one of the components reported to be present in khoyer (Rajendra et al, 2011).…”
Section: Resultscontrasting
confidence: 48%
“…Reduction of serum glucose levels of ethanolic extract by several factors. The extract of bottle gourd may influence in a positive manner the pancreatic secretion of insulin, or the extract may increase the glucose uptake [18], thus reducing the presence of glucose in serum.…”
Section: Anti-hyperglycemic Activity Of Ethanolic Extractmentioning
confidence: 99%
“…Rats were divided in to four groups (n = 6) were administered with distilled water (10 ml/kg), Glibenclamide (standard drug) (10 mg/kg) 10 , and ethanolic extracts (PIELE) at dose of 100 and 200 mg/kg p.o. by help of oral gavages, respectively.…”
Section: Oral Glucose Tolerance Test (Ogtt)mentioning
confidence: 99%
“…Blood glucose levels were measured by withdrawing a drop of blood from tip of the animal tail and placing it on the glucometer strip 10 . The accu-check glucometer with the help of strips gives the digital value of blood glucose level.…”
Section: Preparation Of Drug Solutionmentioning
confidence: 99%